Barriers and facilitators to anal cancer screening among men who have sex with men: a systematic review with narrative synthesis - IatTou Sam; Wen Dang; NgaTeng Iu; ZiYue Luo; Yu-Tao Xiang; Robert David Smith (BMC Cancer)
Abstract Background Increasing trends of anal cancer among men who have sex with men (MSM) highlight the importance of anal cancer screening. However, the screening rate of anal cancer among MSM remains relatively low. This systematic review aims to identify and critically evaluate studies examining barriers and facilitators influencing MSM’s participation in anal cancer screening. Methods Systematic searches were performed in five databases (Web of Science, Medline, Embase, PsycINFO, and CINAHL). Evidence from qualitative, quantitative, and mixed methods studies was extracted and synthesized. Mixed Methods Appraisal Tool (MMAT) was used for quality assessment. Two researchers underwent selection and appraisal independently. PROSPERO registration number: CRD42024601449. Results 305 studies were identified with a total of 32 studies included, including 11 qualitative studies, 18 quantitative studies, and 3 mixed methods studies. The barriers and facilitators to anal cancer screening were categorized into four domains: individual factors, healthcare system factors, healthcare provider factors, and screen-related factors. Among the four domains, the most frequently reported barriers and facilitators to anal cancer screening were individual factors. A lack of knowledge about the risks of HPV, anal cancer, and anal screening (n = 16) was the most significant barrier. In contrast, a greater perceived understanding of anal cancer and screening (n = 6) was identified as the primary facilitator. Conclusions This systematic review provided a comprehensive assessment of barriers and facilitators to anal cancer screening among MSM, highlighting the need for targeted comprehensive intervention programs to enhance acceptance of screening. Implementing effective strategies to address potential barriers and promote facilitators across all domains of public health could significantly increase screening uptake.